Co-criação de valor e orientação para mercado: um estudo em empresas multinacionais estrangeiras e brasileiras - Piccioli, Maria Luiza Vasques (2013)
This study is dedicated to the analysis of the Value Co-Creation Management and its relation to the market oriented strategy in foreign and Brazilian multinational companies. It is based on a theory review in which three main topics are discussed: (1) Marketing concepts evolution and the strategic orientation to market; (2) competitive advantage development and the value co-creation management; (3) foreign and Brazilian multinational companies, subsidiaries' role and the global Marketing management. The qualitative nature research developed on the market used the methodology of multiple case studies, following the protocol proposed by Yin (2001). This study was performed in 4 multinational companies, among them two Brazilian and two foreign ones, directly with the areas that are responsible for value co-creation management. In total, eight interviews were performed, being two per company, between the months of October and December 2012. After analysis, the research pointed not only to market orientation as a predecessor of co-creation management, but also to the value discipline chosen by the company as a strategical driver to co-creation implementation. In relation to Brazilian and foreign multinational companies, it was possible to identify that the management style is related to the organizations characteristics rather than their nationalities. As a contribute, this study fills a gap by bringing closer the subjects of Marketing orientation of co-creation practices and co-creation management in multinational companies.